The religious-intellectual network: the arrival of Islam in the archipelago - Fauzi, Nurulwahidah; Mohammad, Ali; Kayadibi, Saim (Islamic Book Trust, 2011)
The expansion of Islam in the Malay state of Johor, especially as it relates to the roles played by Arabs and Ottomans, is an interesting subject in its own right. The resulting network was based upon the efforts of the ‘ulama’ and the ruler, and especially the Muslim Consultant Jurist (mufti), to establish religious coordination in Johore. This article analyzes this network during the twentieth century and details its historical background. Emphasis is placed on the role played by the ‘ulama’ role and the challenges they faced at that time, based upon the hypothesis that their contribution to Islam’s early expansion and practice in Johor was quite significant.